A saúde física e mental no processo de formação em fisioterapia em uma universidade pública do Paraná: a percepção de alunos e professores - Tavares, Keila Okuda (2024)
Student health is a concern for higher education institutions, as the number of illness cases and their consequences continues to rise. Giving students and professors the opportunity to talk about illness, makes it possible to verify the causes, so that strategies can be implemented with the aim of healthier professional qualification that allows students to achieve full personal and professional development. The general objective of this study was: to verify, from the perspective of the student and the undergraduate physical therapy professor at Unioeste, factors that can promote illness among students during graduation; factors that contribute to not getting sick; strategies that can be used to prevent its appearance. This is exploratory descriptive qualitative research that presents complementary quantitative data; 150 (85.23%) students and 31 (67.39%) professors participated. Data collection was carried out using a questionnaire, from may to august 2021. Quantitative variables were analyzed using simple descriptive statistics and the content of open questions with Content Analysis (Bardin). The ATLAS.Ti software was used as a tool to assist qualitative analysis. The prevalence of physical illnesses and mental disorders among students was 17,33% and 80%, respectively. When synthesizing the participants' responses about the factors that promote illness during graduation, it was observed: professor-student, student-student, student and people working in teaching-learning environments and administrative sectors of the university; the professor's teaching and assessment methods; contact with sick people, their illnesses and practical activities related to the care of these people; background and individual characteristics of the student; students' difficulty in facing negative situations; the physical structure and organization of teaching-learning environments; the bureaucracy of the administrative sectors. Participants, when asked about the factors that contribute to not getting sick, mentioned factors that oppose those identified as predisposing. For example, the presence of interpersonal conflicts between professor and student as an adverse factor, while a harmonious relationship was identified as something beneficial, which helps promote health. When considering the participants' responses about what can be done to prevent illness, it was reported: knowing the students' opinion about the course and the professors; make changes to the curriculum, teaching and assessment methods; improve interpersonal relationships between professors and students and between students; identify cases of mental disorders early; establish new approaches focused on student health; create approaches focused on professor health; expand and better disseminate approaches to student health that already exist; promote discussion about mental health within the university; encourage students to participate in extracurricular activities. The need for an institutional policy was highlighted that aims to improve the pedagogical training of higher education professors, to promote the development of socio-emotional skills among members of the academic community aiming at cooperation and solidarity, to support a healthy lifestyle and to promote a support network for students. xii